Reported foodborne illness and gastroenteritis in Australia: annual report of the OzFoodNet network, 2004 - OzFoodNet Working Group; Kirk, Martyn (Communicable Diseases Intelligence, 2005)
In 2004, OzFoodNet sites recorded 24,313 notifications of eight potentially foodborne diseases, along with 118 outbreaks of foodborne disease. Overall, reports of both notifications and outbreaks were higher than previous years. The most common sporadic diseases were campylobacteriosis (15,640 cases) and salmonellosis (7,842 cases). Reports of sporadic cases of Shiga toxin-producing Escherichia coli were rare with only 46 cases, but there were two small clusters due to serotypes O157/O111 and O86. The 118 foodborne disease outbreaks affected 2,076 persons, of whom 5.6 per cent (116/2,076) were hospitalised and two people died. Foods prepared in restaurants and catering settings caused the most outbreaks and the most common agent was Salmonella Typhimurium. Outbreak investigations during 2004 implicated chicken, foods containing eggs, imported oysters and food handlers infected with norovirus. In addition to foodborne outbreaks, OzFoodNet sites reported 874 outbreaks that were spread from person-to-person affecting 25,363 people. Sites conducted 54 investigations into clusters of Salmonella and other pathogens where a source could not be identified. Surveillance of foodborne diseases continued to improve during 2004, with all jurisdictions contributing to national cluster reports and using analytical studies to investigate outbreaks. Ninety-eight per cent of Salmonella notifications on state and territory surveillance databases recorded complete information about serotype and phage type. Foodborne disease may cost Australia as much as 1.2 billion annually making it vital to intervene to prevent disease. Commun Dis Intell 2005;29:164–191.